Effect of 12-week skill training programme on selected physical fitness indices among secondary school female football players in Makurdi, Benue State, Nigeria - Akameze, J. N.; Tyoakaa, A. A.; Chukwudo, D. U.; Ugwueze, F. C. (American Journal of Sports Science, 2025)
Female participation in football has grown steadily in Nigeria, yet many young female players lack access to structured training that targets key physical fitness components. Aerobic fitness, agility, and leg power are critical for football performance, but there is limited research on how structured skill training programmes affect these variables in adolescent female athletes. This study investigated the effects of a 12-week skill training programme on aerobic fitness, agility, and leg power among secondary school female football players in Makurdi, Benue State, Nigeria. A quasi-experimental design was employed. The study population included 222 female football players from twelve secondary schools registered for the 2024 all-secondary school games. A purposive sample of 40 players from two intact schools was selected. Aerobic fitness was assessed using the Progressive Aerobic Cardiovascular Endurance Run (PACER) test; agility was measured using the Illinois Agility Test; and leg power was evaluated with a jump test. Data were analyzed using Analysis of Covariance (ANCOVA) at a 0.05 significance level. The 12-week skill training programme significantly improved aerobic fitness and agility (p < 0.05). However, the programme did not produce a statistically significant improvement in leg power (p > 0.05). The findings suggest that a structured skill training programme can effectively enhance aerobic fitness and agility in female secondary school football players, though additional interventions may be required to improve leg power. It is recommended that football coaches adopt this type of programme with a focus on overall physical and skill development.